Relationship between family income and child health in Indonesia - Budiman, Dede; Damayanti, Arie (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
This study aims to examine the income-health gradient and empirically test the probability of the dependent variable on the child's health status, especially the role of insurance variables, and maternal variables working on children's health status. The use of these 2 (two) variables aims to reduce the social-economic relationship between family income and children's health status. The results of replication from Park's study (2010) showed different income-health gradient results. In this study the results of income-health gradient occurred in school-age children in the 2000-2007 panel data and income-health gradient occurred in the 2007-2014 panel data for preschool and school-aged children, in contrast to Park's (2010) income-health gradient results. only occurs in preschoolers. The role of insurance variables has not been able to reduce the relationship of family income and children's health, while the working mothers variable can reduce the relationship of family income and child health only on the 2000-2007 panel data. Supervision and improvement of insurance facilities by the government as a solution to improve children's health in an effort to break the chain of intergenerational poverty, and increase the program of increasing the proportion of the population with calorie intake below the consumption level of 1400 kcal / capita / day.